CONSTRUCTION OF SUBSTITUTION BOX (S-BOX) BASED ON IRREDUCIBLE POLYNOMIALS ON GF(2^8) - Tita, Faldy; Setiawan, Adi; Susanto, Bambang (PATTIMURA UNIVERSITY, 2024)
In the field of modern encryption algorithms, the creation of S-Box is an essential element that plays an important role in maintaining data security in various industries. This article provides a comprehensive review of various S-Box designs, with particular emphasis on essential parameters such as “Average ”, “Average ” and “Non-linearity value”. The main goal is to determine the most optimal S-Box structure to minimize correlation, thereby improving the security and unpredictability of the cryptographic system. Research results indicate that the S-Box characterized by the 1BD hexadecimal code is superior to its counterparts. It has an average value of 4.1953 and an average value of 0.4756. In contrast, the S-Box represented by hexadecimal code 169 displays a relatively lower level of security, with an average d value of 3.8750 and an average value of 0.5156. These results enable security experts and cryptographers to make the correct choice when selecting the S-Box with the minimum correlation value, thereby strengthening cryptographic systems against emerging cyber threats.